2020
DOI: 10.1590/s1983-41952020000100011
|View full text |Cite
|
Sign up to set email alerts
|

Concrete beam subjected to shear and torsion: a comparison between the Brazilian Standard Code NBR 6118, ACI and AASHTO Provisions

Abstract: Most of torsion studies available are relative to pure torsion, arising from the exclusive application of a torsion moment in a concrete beam. This situation, however, is only possible in laboratories. In practice, the vast majority of twisted beams are subjected to the combination of shear forces and torsion, which gives rise to a more complex state of stress to be analyzed. The purpose of this paper is to present the provisions of the ACI 318/2014 Codes, AASHTO and ABNT NBR 6118: 2014 related to shear and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…On this basis, it can be found that the strut angle θ ð Þ has significant impact on the analytical accuracy of the torsional design methods. [48][49][50][51] In the torsional design provision of SNiP, θ is not explicitly required to calculate the torsional strength, but the tensile strength ratios of the reinforcements λ 1 ð and λ 2 Þ are limited to guarantee the yielding of reinforcement as presented in Equations ( 16) and (17). Then, these tensile strength ratio λ 1 ð and λ 2 Þ can be regarded as an equivalent expression corresponding to θ SNiP defined by other design codes as presented in Equation (19).…”
Section: Evaluation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, it can be found that the strut angle θ ð Þ has significant impact on the analytical accuracy of the torsional design methods. [48][49][50][51] In the torsional design provision of SNiP, θ is not explicitly required to calculate the torsional strength, but the tensile strength ratios of the reinforcements λ 1 ð and λ 2 Þ are limited to guarantee the yielding of reinforcement as presented in Equations ( 16) and (17). Then, these tensile strength ratio λ 1 ð and λ 2 Þ can be regarded as an equivalent expression corresponding to θ SNiP defined by other design codes as presented in Equation (19).…”
Section: Evaluation Resultsmentioning
confidence: 99%
“…Consequently, the average of θEC2 was as low as 28.4°, while the averages of θEC2,eq and θACI,eq were 39.3° and 42.0°, respectively, which are quite close to the average value of 40.27 ° by the CSA method. On this basis, it can be found that the strut angle ()θ has significant impact on the analytical accuracy of the torsional design methods 48–51 …”
Section: Comparison Of Torsional Design Methodsmentioning
confidence: 99%